2007
DOI: 10.3402/ijch.v66i3.18257
|View full text |Cite
|
Sign up to set email alerts
|

Low birthweight as an indicator of child health in Greenland—use, knowledge and implications

Abstract: Objectives. The aim of this study was to analyse if low birthweight is a valuable indicator of child health in Greenland. Study design. A case study focusing on "low birthweight as an indicator in Greenland" with 3 units and 5 subunits of analyses. Methods. Literature reviews, interviews with health care professionals and an analysis of the National Birth Register. Results. Low birthweight was a well-known and yearly surveyed indicator, but not used by clinicians or by policymakers. Research was sparse, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Two articles were from Greenland, including a review of available child health indicators (22) and a critique on the use of low birth weight as MCH indicator in Greenland (23). Four articles were from Australia and focused specifically on maternal health indicators in the Australian Aboriginal and Torres Strait Islander populations (24–26).…”
Section: Resultsmentioning
confidence: 99%
“…Two articles were from Greenland, including a review of available child health indicators (22) and a critique on the use of low birth weight as MCH indicator in Greenland (23). Four articles were from Australia and focused specifically on maternal health indicators in the Australian Aboriginal and Torres Strait Islander populations (24–26).…”
Section: Resultsmentioning
confidence: 99%
“…Although today, both some of the old and the new diseases seem to be more prevalent in villages and in remote areas. This pattern has been found in rates of suicides, smoking, child mortality, low birth weight, dental health, tuberculosis, and obesity (Aaen-Larsen and Bjerregaard 2003; Office of the Chief Medical Officer in Greenland 2006a;Petersen and Christensen 2006;Niclasen 2007;.…”
Section: The Conceptual Basis Of the Municipal Indicatorsmentioning
confidence: 92%
“…The first is whether these indicators are associated with the same risk and protective factors and can be interpreted the same way as in other developed countries. So far, low birth weight has been evaluated in an in-depth validation study as the only indicator (Niclasen 2007). The study found that the quantitatively most important risk factors were the same as in other developed countries, although special risk factors exist in the Arctic.…”
Section: Use Of Traditional Indicators In the Greenlandic Settingmentioning
confidence: 95%
See 2 more Smart Citations